Artificial Regeneration of Mangroves - Kumar, Rajiv (Indian Forester, 1999)
Mangroves are one of the most productive ecosystems of the tropical coastal areas of the world and are fragile in nature. Despite their ecological significance such as stabilizing the coastal shorelines, guarding the landmass from tidal surges, cyclones, high velocity winds, checking the advancement of sea etc., Mangroves are subjected to unabated exploitation for economic gains. This causes severe stress to its hygiene and survival. In this process of economic exploitation, we lose many areas and it is difficult to regenerate arcas, which are highly degraded. For the proper management and eco-restoration of Mangroves, artificial regeneration is a must to augment areas successfully with right choice of species. Artificial regeneration is utmost important in areas where natural regeneration is a failure or inadequate. This paper describes the various aspects of artificial regeneration from nursery to planting out and analyses the issues involved therein. This is an outcome of the author’s observations based on studies conducted on Mangroves in Goa and Middle Andaman.